ANALYSIS OF THE INFLUENCE OF MARKETING MIX TOWARDS LOYALTY THROUGH COOPERATIVE CUSTOMER SATISFACTION IN SOUTH TANGERANG CITY - Silvia Sari; Sevty Wahiddirani Saputri (EkoPreneur, 2019)
Cooperative as an important pillar in economic development in Indonesia. Cooperatives need to improve their loyalty and customer satisfaction in order to win the competition with other rital businesses. The research aims to identify and analyze forming factors in customer satisfaction that contribute to customer loyalty. This research was conducted in South Tangerang City because there is an increase in the number of cooperative ventures. Primary data was collected through questionnaires to 100 cooperative customers in South Tangerang city with purposive sampling techniques, and data Analyzed with Structural Equation Modeling (SEM). The exogenous latent variable is the marketing Mix (7P). While customer satisfaction and loyalty as an endogenous latent variable. The results showed that the built model has fulfilled the criteria of goodness fit and variable measuring research has a reliability (CR ≥ 0.70, VE ≥ 0.50) which is good. The results of SEM analysis indicate that customer satisfaction is largely influenced by the people dimension (γ = 0.92). The People dimension is well formed by the ability of employees to provide clear information (λ = 0.97), employee appearance (λ = 0.87), fast employee response (λ = 0.84), and employee friendliness (λ = 0.57). This the human resources (people) on cooperative ventures need to be built sustainably and gradually the customer satisfaction proved able to foster cooperative customer loyalty.  Keywords: Customer Satisfaction, Customer Loyalty, Marketing Mix, People, Cooverative